2013
DOI: 10.1021/jp401972h
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Photoelectrochemical Study of Hydrogenated Bismuth Vanadate

Abstract: We demonstrate hydrogenation as a facile method to significantly enhance the performance of BiVO 4 films for photoelectrochemical water oxidation. Hydrogenation was performed for BiVO 4 films by annealing them in hydrogen atmosphere at elevated temperatures between 200 and 400 °C. Hydrogen gas can reduce BiVO 4 to form oxygen vacancies as well as hydrogen impurities. DFT calculation predicted that both oxygen vacancies and hydrogen impurities are shallow donors for BiVO 4 with low formation energies. These def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
240
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(264 citation statements)
references
References 65 publications
22
240
1
1
Order By: Relevance
“…Wang and co-workers have previously calculated formation energies for hydrogen interstitials (H int ) and substitutional hydrogen on oxygen lattice sites (H O ), as well as for native defects, in BiVO 4 . 23 They found that the formation energy for H int is lower than for all other defects under nearly all conditions. In addition, the formation energy of H O is low compared to native defects under the O-poor conditions encountered during H 2 annealing.…”
Section: Hydrogen Incorporation In Bivomentioning
confidence: 97%
See 3 more Smart Citations
“…Wang and co-workers have previously calculated formation energies for hydrogen interstitials (H int ) and substitutional hydrogen on oxygen lattice sites (H O ), as well as for native defects, in BiVO 4 . 23 They found that the formation energy for H int is lower than for all other defects under nearly all conditions. In addition, the formation energy of H O is low compared to native defects under the O-poor conditions encountered during H 2 annealing.…”
Section: Hydrogen Incorporation In Bivomentioning
confidence: 97%
“…36 Both hydrogen defect types act as donors in BiVO 4 and can contribute to the n-type conductivity of the material. 23 This is particularly important for synthesis of BiVO 4 . As described above, native defect theory would predict that material synthesized under Orich conditions, which is the typical environment used for formation of BiVO 4 , should exhibit p-type character.…”
Section: Hydrogen Incorporation In Bivomentioning
confidence: 99%
See 2 more Smart Citations
“…[23] It is also found to dramatically improve the PEC water splitting performance of other metal oxides, including the currently highest performing metal oxide photoanode, BiVO4. [24][25][26][27][28] The improved performance was initially assumed to originate from the increased electrical conductivity due to oxygen vacancy formation and/or hydrogen insertion (i.e., an increase in carrier density through donor doping). [23][24][25][26][27][28][29] However, to the best of our knowledge, no report has yet provided direct evidence for the influence of hydrogen treatment on the carrier transport properties of BiVO4.…”
Section: Introductionmentioning
confidence: 99%